THE MARKET OF LEARNING SERVICES IN UZBEKISTAN AND THE IMPACT OF STUDENT LOANS THEREUPON - Rasulov Akmal Abdunaimovich (Scholar Express Journals, 2024)
The aim of this research paper is to analyze the current state of the learning services market in Uzbekistan, focusing on public and non-public (private) institutions at different levels of education. This analysis is of the scientific significance in the development of policies that raise the current state and quality of education in Uzbekistan, as well as competitiveness. In addition, the article presents the author’s analytical comments.
Keywords: education; student loan; student